2013
DOI: 10.3402/gha.v6i0.18894
|View full text |Cite
|
Sign up to set email alerts
|

‘Elastic band strategy’: women's lived experience of coping with domestic violence in rural Indonesia

Abstract: BackgroundExperiencing domestic violence is considered a chronic and stressful life event. A theoretical framework of coping strategies can be used to understand how women deal with domestic violence. Traditional values strongly influenced by religious teachings that interpret men as the leaders of women play an important role in the lives of Javanese women, where women are obliged to obey their husbands. Little is known about how sociocultural and psychosocial contexts influence the ways in which women cope w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 9 publications
0
32
0
14
Order By: Relevance
“…In the third subcategory, conflict could be evaded by doing as one was told and putting one’s own needs last. These strategies resemble the strategies for maintaining harmony by women exposed to controlling or violent behavior in other settings [35]. Following this lowest path, women risk facing continued dependency of their partners and difficulties to maintain a strong self in long run.…”
Section: Discussionmentioning
confidence: 99%
“…In the third subcategory, conflict could be evaded by doing as one was told and putting one’s own needs last. These strategies resemble the strategies for maintaining harmony by women exposed to controlling or violent behavior in other settings [35]. Following this lowest path, women risk facing continued dependency of their partners and difficulties to maintain a strong self in long run.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14] Very few qualitative studies discussed the relationship dynamics between the abusive husband and wife. [15][16][17][18][19][20] Studies from developing countries demonstrated that the women experienced a conflict of emotions and developed coping mechanisms. They did not want to leave their abusing partners due to patriarchal society, financial dependency on husbands, fear and considering violence as normal behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] Studies from developing countries demonstrated that the women experienced a conflict of emotions and developed coping mechanisms. They did not want to ABSTRACT Background: The prevalence of intimate partner violence (IPV) contributed to reproductive health problems worldwide.…”
mentioning
confidence: 99%
“…Perempuan Jawa sering diposisikan sebagai perempuan yang selalu patuh pada suaminya. Konflik dalam rumah tangga harus disembunyikan rapat-rapat, karena hal itu adalah aib keluarga (Hayati, Eriksson, Hakimi, Hoggberg & Emmelin, 2013). Jadi perempuan Jawa terbiasa menjadi subordinat dalam kehidupan sehari-hari.…”
unclassified
“…KDRT merupakan bentuk pengingkaran bahwa manusia itu adalah makhluk yang terus berkembang (UNICEF, 2000). KDRT cenderung seperti usahausaha untuk merendahkan manusia secara berkesinambungan berdasarkan alasanalasan yang nampaknya pro-perempuan seperti menjaga martabat perempuan (Hayati et al, 2013). Penelitian ini juga ingin memperlihatkan bahwa perasaan learned helplessness (perasaan tidak berdaya sebagai akibat proses belajar) yang sering terjadi pada perempuan korban KDRT, ternyata bisa dilawan oleh perempuan itu sendiri (Higgins, 2011).…”
unclassified